2016
DOI: 10.23937/2474-3690/1510016
|View full text |Cite
|
Sign up to set email alerts
|

MyHEART: A Non Randomized Feasibility Study of a Young Adult Hypertension Intervention

Abstract: BackgroundIn the United States, young adults (18–39 year-olds) have the lowest hypertension control rates (35%) compared to middle-aged (58%) and older (54%) adults. Ambulatory care for hypertension management often focuses on medication with little time for self-management and behavioral counseling. This study was designed to evaluate the feasibility of MyHEART, a telephone-based health coach self-management intervention for young adults. The goals were to determine the intervention’s ability to: 1) recruit y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 32 publications
(34 reference statements)
0
26
0
Order By: Relevance
“…Unfortunately, young adults may have difficulty in adhering to the recommended frequency as a result of visit copayments, childcare needs, school, and/or work schedules. Prior studies have suggested using telephone follow‐up and team‐based care to bridge follow‐up visits and support hypertension care delivery in this hard‐to‐reach population.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, young adults may have difficulty in adhering to the recommended frequency as a result of visit copayments, childcare needs, school, and/or work schedules. Prior studies have suggested using telephone follow‐up and team‐based care to bridge follow‐up visits and support hypertension care delivery in this hard‐to‐reach population.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies [ 31 , 32 , 37 ] that informed the MyHEART website development were approved by the University of Wisconsin-Madison Health Sciences Institutional Review Board (IRB) and informed consent was obtained from patient and clinician stakeholders. Neither IRB approval nor written consent were needed to design or implement this website because the data that informed MyHEART development was already described in the original IRB submission for the prior studies.…”
Section: Methodsmentioning
confidence: 99%
“…The names and contact information of potentially eligible patients were made available to the respective study coordinators at each site. The site coordinators will mail an introductory research packet, which was designed by racially/ethnically diverse patient stakeholders, approved by primary care leaders, and used in the pilot study [48]. The introductory packet includes a flyer summarizing MyHEART and a pre-paid opt-out postcard.…”
Section: Participant Recruitment and Eligibility Screeningmentioning
confidence: 99%
“…To address the unmet need in hypertensive care for young adults, we developed MyHEART (My Hypertension Education And Reaching Target), a multi-component, theoretically-based intervention designed to achieve self-management among young adults with uncontrolled hypertension [48]. MyHEART is a patient-centered program that uses evidence-based health behavior approaches to lower blood pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation